Political instability and tourism: An empirical study with special reference to the microstate of cyprus - Seddighi, H. R.; Theocharous, Antonis L.; Nuttall, M. W. (My University, 2002)
Political instability is characterised by a multifaceted and complex character and its existence and impact in various countries is multilevel and multidimensional. The need for assessment, evaluation and analysis of the various interrelationships between political instability and the tourism industry is essential considering the sensitive nature of the tourism industry, the ever-increasing competition, and the very narrow profit margins. This study provides an exploratory model for the identification and analysis of the theoretical and empirical dimensions of political instability that are related to the tourism industry of Cyprus. Twenty-eight variables were selected as ‘candidate indicators’ of political instability. The selected variables were included in a questionnaire that was distributed to travel agents in Cyprus. Factor analysis was employed and four dimensions of political instability emerged which were interpreted according to the particularities and individual characteristics of the tourism industry of Cyprus. © 2002, Taylor & Francis Group, LLC. All rights reserved.
Keywords: Cyprus tourism industry; Dimensional structures; Political instability; Tourism; Tourism planning